How is 1/(x-2) = (2x - 6)/(x + 6) + 1 rewritten as 1/(x - 2) = 3x/(x + 6)? I don't understand.

1 answer

1 = (x+6)/(x+6)

so, the right hand side becomes

((2x-6)+(x+6))/(x+6)
= 3x/(x+6)
Similar Questions
    1. answers icon 1 answer
  1. Sort the cards according to whether each expression can be rewritten as 6 ^ 8Cannot be rewritten as 6 ^ 8 Can be rewritten as 6
    1. answers icon 3 answers
  2. Does log eqaul to baswe 10?So would logb=a be rewritten as 10^a=b? AND Why would ln5=x be rewritten as e^x=5? is it because ln
    1. answers icon 0 answers
    1. answers icon 1 answer
more similar questions